A method for estimating rainflow fatigue damage of narrowband non-Gaussian random loadings. (October 2014) - Cheng, HW; Tao, JY; Chen, X; Jiang, Y
We describe efforts to improve the accuracy of fatigue damage estimation methods of narrowband non-Gaussian random loading. The available analytical solutions are reviewed and briefly summarized, and the reasons for the occurrence of computational errors during nonlinear transformation-based methods are determined. The computational errors are mainly due to inconsistencies in the statistical moments above fourth order. A new approach is proposed for the evaluation of rainflow fatigue damage. This approach avoids the problem of transformation-based methods and provides accurate estimation for fatigue damage of narrowband leptokurtic non-Gaussian random loading. Additionally, the applicability of the proposed method to Gaussian random loading is investigated. Finally, two examples are carried out and comparisons are made to more commonly used methods to demonstrate the capabilities and brevity of the proposed algorithm.